USEFUL ASPECTS OF MEDICINAL PLANTS AND PLACES OF USE - Odiljonov, Khojiakbar Zakirjon ugli (Innovative Development in Educational Activities, 2022)
In this article, the description, classification, composition and useful aspects of medicinal plants that have been used in recent days and in the past have been clarified, and the places of use have been determined. During the writing of this article, comparison, calculation, experimental and historical methods were used and the intended goal was achieved.